(untitled) (Fiep Bulletin - online, 2015)
In April 1952, at the central gymnastic Institute (for the first time at this institute), P. – O. Ãstrand defended a thesis in order to gain the Doctor of medicine degree. This thesis is of great interest and the author´s summary of that part of the thesis, which deals with the suitability of school sporte for different ages and sexes, is given below.